ADVANCEMENTS IN THERMO ELASTIC MODELS: APPLICATIONS IN HOMOGENEOUS AND NON-HOMOGENEOUS ELASTIC MEDIA - Yadav, Ritesh; Kumari, Bharti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the latest advancements in thermoelastic models with a focus on their applications in both homogeneous and non-homogeneous elastic media. Thermoelasticity, which combines principles of thermodynamics and elasticity, has evolved significantly, enabling the study of complex systems subjected to thermal and mechanical interactions. The study highlights theoretical developments, numerical methods, and experimental validations, providing insights into their relevance across various engineering and scientific disciplines. Thermoelastic models have been widely used to study the behavior of elastic media under thermal and mechanical loads. Recent advancements in these models have enabled the simulation of complex phenomena in homogeneous and non-homogeneous elastic media. This paper provides a comprehensive review of the latest developments in thermoelastic models and their applications in various fields. We discuss the theoretical foundations of thermoelasticity, the development of new constitutive models, and the application of these models to simulate the behavior of homogeneous and non-homogeneous elastic media.